Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To evaluate the piecewise function [tex]\( f(x) \)[/tex] at the given values, we need to follow the definition of [tex]\( f(x) \)[/tex] and substitute each value into the appropriate expression. The piecewise function is defined as:
[tex]\[ f(x) = \left\{ \begin{array}{ll} 4x + 4 & \text{if } x < 0 \\ 3x + 6 & \text{if } x \geq 0 \end{array} \right. \][/tex]
Let's evaluate the function at the specified values:
(a) [tex]\( f(-4) \)[/tex]
Since [tex]\(-4 < 0\)[/tex], we use the expression [tex]\( f(x) = 4x + 4 \)[/tex]:
[tex]\[ f(-4) = 4(-4) + 4 = -16 + 4 = -12 \][/tex]
Therefore, [tex]\( f(-4) = -12 \)[/tex].
(b) [tex]\( f(0) \)[/tex]
Since [tex]\(0 \geq 0\)[/tex], we use the expression [tex]\( f(x) = 3x + 6 \)[/tex]:
[tex]\[ f(0) = 3(0) + 6 = 0 + 6 = 6 \][/tex]
Therefore, [tex]\( f(0) = 6 \)[/tex].
(c) [tex]\( f(1) \)[/tex]
Since [tex]\(1 \geq 0\)[/tex], we use the expression [tex]\( f(x) = 3x + 6 \)[/tex]:
[tex]\[ f(1) = 3(1) + 6 = 3 + 6 = 9 \][/tex]
Therefore, [tex]\( f(1) = 9 \)[/tex].
So the values of the function [tex]\( f(x) \)[/tex] at the given points are:
(a) [tex]\( f(-4) = -12 \)[/tex]
(b) [tex]\( f(0) = 6 \)[/tex]
(c) [tex]\( f(1) = 9 \)[/tex]
[tex]\[ f(x) = \left\{ \begin{array}{ll} 4x + 4 & \text{if } x < 0 \\ 3x + 6 & \text{if } x \geq 0 \end{array} \right. \][/tex]
Let's evaluate the function at the specified values:
(a) [tex]\( f(-4) \)[/tex]
Since [tex]\(-4 < 0\)[/tex], we use the expression [tex]\( f(x) = 4x + 4 \)[/tex]:
[tex]\[ f(-4) = 4(-4) + 4 = -16 + 4 = -12 \][/tex]
Therefore, [tex]\( f(-4) = -12 \)[/tex].
(b) [tex]\( f(0) \)[/tex]
Since [tex]\(0 \geq 0\)[/tex], we use the expression [tex]\( f(x) = 3x + 6 \)[/tex]:
[tex]\[ f(0) = 3(0) + 6 = 0 + 6 = 6 \][/tex]
Therefore, [tex]\( f(0) = 6 \)[/tex].
(c) [tex]\( f(1) \)[/tex]
Since [tex]\(1 \geq 0\)[/tex], we use the expression [tex]\( f(x) = 3x + 6 \)[/tex]:
[tex]\[ f(1) = 3(1) + 6 = 3 + 6 = 9 \][/tex]
Therefore, [tex]\( f(1) = 9 \)[/tex].
So the values of the function [tex]\( f(x) \)[/tex] at the given points are:
(a) [tex]\( f(-4) = -12 \)[/tex]
(b) [tex]\( f(0) = 6 \)[/tex]
(c) [tex]\( f(1) = 9 \)[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.